Dynamic of centromere associated RNAs and the centromere loading of DNA repair proteins in growing oocytes - Yang, Lin-Li; Li, Yan-Chu; Xia, Tian-Jin; Li, Sen; Feng, Xie; Li, Chao; Xie, Feng-Yun; Ou, Xiang-Hong; Ma, Jun-Yu (Frontiers in Genetics, 2023)
Mammalian centromeres are generally composed of dispersed repeats and the satellites such as α-satellites in human and major/minor satellites in mouse. Transcription of centromeres by RNA polymerase II is evolutionary conserved and critical for kinetochore assembly. In addition, it has been found that the transcribed satellite RNAs can bind DNA repair proteins such as MRE11 and PRKDC, and excessively expressed satellite RNAs¬ could induce genome instability and facilitate tumorigenesis. During the maturation of female oocyte, centromeres are critical for accurate segregation of homologous chromosomes and sister chromatids. However, the dynamics of oocyte centromere transcription and whether it associated with DNA repair proteins are unknown. In this study, we found the transcription of centromeres is active in growing oocytes but it is silenced when oocytes are fully grown. DNA repair proteins like Mlh1, Mre11 and Prkdc are found associated with the minor satellites and this association can be interfered by RNA polymerase II inhibitor α-amanitin. When the growing oocyte is in vitro matured, Mlh1/Mre11/Prkdc foci would release from centromeres to the ooplasm. If the oocytes are treated with Mre11 inhibitor Mirin, the meiosis resumption of growing oocytes with Mre11 foci can be suppressed. These data revealed the dynamic of centromeric transcription in oocytes and its potential association with DNA repair proteins, which provide clues about how oocytes maintain centromere stability and assemble kinetochores.